How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode